Physiological response of Solanum crinitum Lam. to contrasting light environments - Dias-Filho, Moacyr Bernardino (Pesquisa Agropecuaria Brasileira, 1997)
During a 66-day period, a study was made in controlled environment chambers, under high (800-1000 µmol m-2 s-1) and low (200-350 µmol m-2 s-1) light regimes on the physiology, morphology and growth of Solanum crinitum, a pioneer medium-sized woody species known to invade forest gaps, active pastures and abandoned agricultural areas in the Brazilian Amazonia. The objective was to investigate the sun-shade acclimation characteristics of this species. High-light grown plants (HL) had higher light saturated rates of photosynthesis than low-light plants (LL). No significant difference in dark respiration was observed between light regimes. Relative growth rate was initially (at 22 d) higher for HL, becoming similar between treatments in the last two harvests (44 and 66 d). Leaf area ratio and specific leaf area were higher for LL. Allocation of biomass to leaves was similar between treatments, while biomass allocated to roots was higher in HL. Allocation of biomass to stems was higher in LL. Leaves grown under high irradiance had less nitrogen per unit of mass and more per unit of area than leaves developed at low irradiance. These results suggest that light is important to the performance of this species and that the differential responses to light conditions may contribute to or detract from its ability to succeed in natural and agricultural environments or to endure control strategies.